A Feedback Control of Fluctuations in Simple Molecular Dynamics. Issue 18 (2015) - Ando, Hiroyasu; Kobayashi, Miki U.
Abstract: Suppression of diffusion processes generated by fluctuations in small-scale systems is crucial for its manipulation especially in nanotechnology. In this work, we focus on thermal fluctuations and their diffusion effect in a model of molecular dynamics. First, we propose time-delayed feedback control method instead of decreasing temperature which is a conventional way of controlling thermal fluctuations. We investigate numerically an effect of delayed-feedback on random walks in discrete time systems and find that diffusion processes of the controlled random walk is suppressed with increasing delay time. Second, we apply the proposed method to simple models of molecular dynamics which are composed of a single particle as well as two flocculated ones with the Lennard-Jones potential. Numerical simulations of the molecular dynamics show the effectiveness of the proposed method for suppressing diffusion processes observed in molecular dynamics.